Composite Lymphoma Containing Mantle Cell and Peripheral T-cell Lymphoma, Not Otherwise Specified: A Report of 2 Cases Treated With Up-front Autologous Stem Cell Transplantation. Issue 10 (November 2020) - González-Gascón y Marín, Isabel; Menarguez, Javier; Kwon, Mi; Burdaspal, Ana; Martínez-Laperche, Carolina; Castro, Yolanda; Infante, María Stefania; Díez-Martín, José-Luis; Hernández-Rivas, José-Ángel
Abstract : We report 2 cases of composite lymphoma comprising mantle cell lymphoma and peripheral T-cell lymphoma, not otherwise specified, a rare association that has only been reported twice in the literature. In case 1, a 64-year-old woman presented with massive splenomegaly and lymphadenopathy. Immunohistochemical studies of the lymph node biopsy suggested the presence of 2 lymphomas, a predominant component of a peripheral T-cell lymphoma, not otherwise specified and an in situ mantle cell neoplasia. These suspicions were confirmed with polymerase chain reaction and fluorescence in situ hybridization studies. In case 2, a 45-year-old man presented with an enlarged right tonsil. Contrary to case 1, the biopsy suggested a predominant infiltration of a classical mantle cell lymphoma and an atypical proliferation of T cells. Biclonality was also confirmed with fluorescence in situ hybridization and molecular techniques. Both cases were treated with an up-front autologous stem cell transplantation after achieving first complete remission, and they remained free of disease for a long period of time. Abstract : Supplemental Digital Content is available in the text.